Efficacy of a novel topical combination of esafoxolaner, eprinomectin and praziquantel against fleas in cats, under field conditions - Tielemans Eric; Otsuki Tomoko; Cheesman Tara; Selmes Fiona; Pfefferkorn Anthony; Prullage Joe (Parasite, 2021)
Esafoxolaner is a purified afoxolaner enantiomer with insecticidal and acaricidal properties. It is combined with eprinomectin and praziquantel, nematodicidal and cestodicidal compounds, in a novel topical endectoparasiticide formulation for cats. This novel formulation was tested in four field studies, in the United States, Europe, Japan and Australia. In all studies, naturally flea-infested domestic cats were treated with the novel formulation at the label dose and conditions of use. The main objective, identical in the four studies, was to assess efficacy on fleas, based on comparison of mean number of fleas found on infested cats before and one month after treatment. Tolerance to the product was also evaluated in the four studies. Otherwise, the studies had some differences in their design and secondary objectives, for example testing for a reduction in flea infestation-related cutaneous signs, testing of one treatment or of three monthly treatments, and use of a positive control group. In the four studies, a total of 307 cats were treated with the novel formulation. The reduction of fleas one month after treatment was 97.7%, 98.8%, 100% and 99.7% in the United States, Europe, Japan and Australia, respectively. There were no significant health abnormalities attributed to treatment in any of the studies.